Pediatric dermatoses pattern at a Brazilian reference center - Isadora Zago Miotto; Vanessa Rolim Bessa; Luana Barreto de Almeida Vasconcelos; Luciana Paula Samorano; Maria Cecília Rivitti-Machado; Zilda Najjar Prado de Oliveira (Elsevier, 2021)
Objective: The aim of this study was to identify the pattern of pediatric dermatoses of patients evaluated at a dermatologic clinic of a reference center in Brazil and to compare these results to similar surveys conducted in other countries. Methods: A retrospective study was performed of patients up to 18 years old, evaluated at a dermatologic clinic between January 1, 2017 and December 31, 2017. Variables collected for analysis included age, gender, dermatological diagnosis, multidisciplinary follow-up, hospitalization, and complementary exams. Results: A total of 2330 patients were included for analysis, with a mean age of 9.7 years. 295 patients were diagnosed with more than one skin disease, leading to a total of 2668 diagnoses. Skin diseases were organized into categories and inflammatory dermatoses corresponded to the largest group (31.2%), mostly due to atopic dermatitis (18.3%). The other main categories were: genodermatoses (14.2%), infectious diseases (12.6%), adnexal disorders (12.5%), cysts and neoplasms (10.7%), and vascular disorders (7.0%). Fifty-six patients needed to be admitted to the dermatology ward; 25 of them (44.6%) for management of worsening of the skin disease, mainly atopic dermatitis, psoriasis, and drug reactions. There were 885 biopsies performed in 38.0% of the subjects and 751 patients (32.2%) required multidisciplinary care; most of them had some genodermatoses. Conclusions: Dermatologic disorders are very common in the pediatric age group and differ from those in adults, suffering influence from cultural, ethnic, socioeconomic, and environmental factors. Knowing the magnitude and distribution of these dermatoses is important to better plan healthcare policies.